T cells cooperate with passive antibody to modify Cryptococcus neoformans infection in mice - Yuan, RuiRong (The National Academy of Sciences of the USA, 1997)
Cryptococcus neoformans is an encapsulated fungus that is a major cause of meningitis in patients with AIDS. In immunocompetent mice, administration of IgG1 mAb protects against cryptococcal infection, whereas administration of IgG3 is not protective and can accelerate the infection. In beige mice with impaired natural killer cell function, the effects of IgG1 and IgG3 are similar to those observed in immunocompetent mice, suggesting that natural killer cells are not crucial for antibody-mediated modulation of cryptococcal infection. In mice lacking CD4(+) T cells, IgG1 is not protective and IgG3 accelerates infection, indicating that CD4(+) T cells are required for antibody-mediated protection. In mice lacking CD8(+) T cells, both IgG1 and IgG3 antibodies prolong survival, indicating that acceleration of the disease process by IgG3 involves CD8(+) T cells. Both IgG1-mediated protection and IgG3-mediated acceleration of infection require interferon γ. These results reveal a functional dependence of passively administered antibody on cellular immunity in cryptococcal infection in mice and have implications for antibody-based therapies in humans in the setting of CD4(+) lymphopenia.